2015
DOI: 10.1101/gr.192229.115
|View full text |Cite
|
Sign up to set email alerts
|

Functional compensation among HMGN variants modulates the DNase I hypersensitive sites at enhancers

Abstract: DNase I hypersensitive sites (DHSs) are a hallmark of chromatin regions containing regulatory DNA such as enhancers and promoters; however, the factors affecting the establishment and maintenance of these sites are not fully understood. We now show that HMGN1 and HMGN2, nucleosome-binding proteins that are ubiquitously expressed in vertebrate cells, maintain the DHS landscape of mouse embryonic fibroblasts (MEFs) synergistically. Loss of one of these HMGN variants led to a compensatory increase of binding of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
80
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(92 citation statements)
references
References 49 publications
12
80
0
Order By: Relevance
“…Likewise, HMGN2 and H1 have also been implicated in enhancer function. Knock-out of Hmgn1 and Hmgn2 in mouse embryo fibroblasts results in the loss of DNase I-hypersensitive sites, particularly at enhancer regions (63). In breast cancer cells, the depletion of certain H1 subtypes, including H1.2, is associated with histone marks indicative of strong enhancers (37).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, HMGN2 and H1 have also been implicated in enhancer function. Knock-out of Hmgn1 and Hmgn2 in mouse embryo fibroblasts results in the loss of DNase I-hypersensitive sites, particularly at enhancer regions (63). In breast cancer cells, the depletion of certain H1 subtypes, including H1.2, is associated with histone marks indicative of strong enhancers (37).…”
Section: Discussionmentioning
confidence: 99%
“…As elaborated below, this octapeptide serves as the anchoring point of HMGNs on the nucleosome [20]. Genome wide, HMGN proteins preferentially bind to DNase I hypersensitive sites, the hallmark of regulatory chromatin sites [2123]. HMGNs have been shown to modulate the global and local structure of chromatin [24], and the levels of histone modifications [25, 26], factors which may be involved in their ability to affect gene expression [27].…”
Section: Hmg Proteinsmentioning
confidence: 99%
“…Results from yeast (Weiner et al 2010;Xi et al 2011;Kubik et al 2015), plants (Vera et al 2014), mouse (Lombraña et al 2013;Deng et al 2015;Iwafuchi-Doi et al 2016;Mieczkowski et al 2016), worm (Ooi et al 2010), and fly (Henikoff et al 2009; have identified highly labile nucleosomes in 5 ′ and 3 ′ "nucleosome-free" regions. In yeast, Xi et al (2011) observed that fragile nucleosomes were associated with H2A.Z-containing promoter nucleosomes, believed to be involved in stress response (Li et al 2005;Zhang et al 2005).…”
Section: Mnase-resistant Nucleosomes Tend To Be In Gene Bodies and Comentioning
confidence: 99%